Analysis of incidental prostate acinar adenocarcinoma: a single-center retrospective study - Eriten, Berna; Yüvrük, Meryem; Gürbüzel, Mihriban; Arıcan, Çiğdem Dicle; Sinanoğlu, Orhun (The European Research Journal, 2025)
Objective: Our study was conducted in a single center to evaluate the characteristics of prostate acinar adenocarcinoma. Methods: A retrospective archive search was conducted between January 1, 2018 and September 1, 2024, and 900 prostate transurethral resection (TUR) and 127 open prostatectomy materials were examined. A total of 43 TUR and 9 open prostatectomy materials were found to have prostatic acinar adenocarcinoma. Results: The ages of the patients were between 51-90. Gleason scores ranged from 3+3:6 to 5+5:10. In immunohistochemical analyses, Alpha methylacyl CoA racemase (AMACR) positivity and p63 negativity were prominent as characteristic findings. Lymphovascular invasion was rarely observed, while perineural invasion was detected more frequently. Conclusions: The importance of histopathological and immunohistochemical features in determining the diagnostic and prognostic factors of prostate acinar adenocarcinoma was investigated in our study. This study may contribute to the literature on prostate cancer diagnostic and treatment strategies and may provide contributions for future research.